The Influence of Transformational Leadership, Work Motivation and Work Discipline on Employee Performance at PT. SMA Aek Nabara - Yuli Apriani; Zulkifli Musannip Efendi Siregar; Siti Lam'ah Nasution (PT Mattawang Mediatama Solution, 2023)
In this era full of competition, companies are trying their best to compete and win the market. Winning the competition does not necessarily happen if the company's internal parties do not try their best to make it happen. One of the company's internal elements that has a big role in achieving company goals is employees. In the current modern industrial era, employees are considered to be the company's most important asset, because employees who work optimally are able to make a positive contribution to achieving company goals. In this study, researchers want to analyze the factors that are predictors of achieving optimal employee performance. Contextually, researchers assess co-worker support, work motivation and work discipline have a positive and significant impact on employee performance at PT. Aek Nabara High School. This research is an explanatory research that examines the relationship between variables, the approach used is a quantitative approach and the analytical tool uses a survey which is distributed to 100 employees of PT.SMA Aek Nabara. Data analysis was performed using SPSS software. The results of this study indicate that transformational leadership has a positive and significant effect on employee performance at PT. SMA Aek Nabara. Work motivation has a positive and significant effect on employee performance at PT. SMA Aek Nabara. Work Discipline has a positive and significant effect on employee performance at PT. SMA Aek Nabara.